Changing Stages of System Innovation at The Ombilin’s Coal Mines of Sawahlunto: From Ghost Town To World Heritage - Erwiza Erman (STI Policy and Management Journal, 2020)
This paper is about system innovation, a transition from one socio-technical system to another by transforming the historical and cultural area into a world heritage city. The objective of this study is to reconstruct the changing stages of system innovation in achieving the status World heritage at the Ombilin coal mines site of Sawahlunto. The stages of transforming the historical and cultural area into a world heritage for tourism space involved multi-dimensional changes, namely: i. transformation of government sector, ii. economic development trajectory, iii. social-political transformation of society. The success key factors  for Ombilin as World Heritage city are: first, the key to the success cannot be separated from the leadership,  second, the heritage asset factor that articulated by leadership success in integrating various interests of actors to revitalize heritage assets. This study of system innovation will contribute to: I  enrich the  understanding on system innovation from historical perspective, and: ii.  new approach in social history through study of achieving the status as a city of World Heritage. Key words: system innovation, World heritage,  coal mining, historical reconstruction, transformation.